Radiation imaging using a compact Compton camera inside the Fukushima Daiichi Nuclear Power Station building. Issue 9 (2nd September 2018) - Sato, Yuki; Tanifuji, Yuta; Terasaka, Yuta; Usami, Hiroshi; Kaburagi, Masaaki; Kawabata, Kuniaki; Utsugi, Wataru; Kikuchi, Hiroyuki; Takahira, Shiro; Torii, Tatsuo
ABSTRACT: The Fukushima Daiichi Nuclear Power Station (FDNPS), operated by Tokyo Electric Power Company Holdings, Inc., went into meltdown in the aftermath of a large tsunami caused by the Great East Japan Earthquake of 11 March 2011. The measurement of radiation distribution inside the FDNPS buildings is indispensable to execute decommissioning tasks in the reactor buildings. We conducted a radiation imaging experiment inside the turbine building of Unit 3 of the FDNPS by using a compact Compton camera and succeeded in visualizing high-dose contamination (up to 3.5 mSv/h). In addition, we drew a three-dimensional radiation distribution map inside the turbine building by integrating the radiation image resulting from the Compton camera into the point cloud data of the experimental environment acquired using a scanning LRF. The radiation distribution map shows the positions of these contaminations on a real space image of the turbine building. The radiation distribution map helps workers to easily recognize radioactive contamination and to decrease their own exposure to radiation because the contamination cannot be observed with the naked eye.